Race, law, and culture : reflections on Brown v. Board of Education - Sarat,Austin(Editor) (Oxford University Press, 1997)
In Race, Law, and Culture, Austin Sarat and others take the continuing controversy about race in law and culture as an invitation to revisit Brown and use this case as a lens through which to view that controversy and the issues involved in it. Revealing how Brown is implicated in America's persistent uncertainties about race, the essays in this book address crucial questions about race, law, and culture in contemporary America, such as: What were the legal and cultural visions contained in Brown?